Ethnic identity of Chinese parents and choice of national and national type primary school - Lee, Diana Phooi Yan; Ting, Su Hie (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The study examined the strength of ethnic identity among the Chinese parents in Malaysia and the relationships between ethnic identity and their choice of school for their children primary education. It is believed that ethnic identity is a crucial factor that influences parents’ choice of school in multi-ethnic societies. Thus, this study was conducted to determine whether the strength of ethnic identity affects parental choice of school. The questionnaire used encompassed Ethnic Identity Scale and Familial Ethnic Socialisation Scale, Rosenberg’s (1979) self-esteem scale. The participants were Chinese parents who send their children to Chinese- and Malay-medium primary school. The results showed that the Chinese parents who chose Mandarin- medium primary school had stronger ethnic identity than parents who chose Malay-medium primary school. Furthermore, familial ethnic socialisation was a strong predictor of ethnic identity for parents who chose Mandarin- medium primary school whereas self-esteem moderately predicted the ethnic identity for both groups of parents. To sum up, this study showed that it is crucial to consider the importance of ethnic identity as an influential factor when examining the parents’ choice of school in a multi-ethnic setting.